Potential of banana peels and sugarcane bagasse as lost circulation material additive in drilling mud application / Norizzatul Akmal Ismail @ Azhar - Ismail @ Azhar, Norizzatul Akmal (2017)
Loss circulation occurs when drilling fluid known as mud, flows into fractures of formations and not able to recirculate in oil and gas well drilling process. This can be a serious problem in maintaining the structure of formations and pressure of the well during drilling activities. Loss of expensive mud could leads to a major financial problem in executing a drilling project. This is why loss circulation is one of the biggest problem that are need to be tackled during drilling. This leads to the focus of this paper on developing new lost circulation material in water-based mud and considering the environmental resulting issues. The objective of this paper are to conduct parametric study of banana peels and sugarcane bagasse as lost circulation material additive for drilling mud application and to investigate thermal stability of the formulated banana peels and sugarcane bagasse based lost circulation material additive for drilling mud. The performance of banana peel and sugarcane bagasse with different particle size and concentration are tested using Fann Viscometer and Low Pressure Low Temperature (LPLT). The performance of the banana peels in rheological properties and filtration properties studies are more efficient compared to the sugarcane bagasse and mud without LCM.